Price discrimination factors for competitive non-regulated taxi markets - Arellano Bahamonde, Rolando José (2018)
The lack of information on price discrimination regarding which characteristics of the client are used and how they influence the definition of the initial price offered in a competitive non-regulated taxi market is the main problem that encouraged this investigation. The study differs from other studies in its use of an experimental research method which allowed analysis of the problem as close as possible to the natural context of the phenomenon. Interviews with 10 taxi drivers produced six variables affecting the process of price definition. A group of 16 people matching those variables collected rates offered by a random sample of taxi drivers. Due to the lack of normality in the distribution of the prices collected, an ordered regression model was implemented. The findings are that price discrimination exists in a nonregulated market such as that of taxis in Lima and that phenotype and the accent of the client are individual characteristics that have a significant influence on the initial price offer. The results confirm that price discrimination is applied in a context like the one of the study, but the question remains as to why it is naturally present and what conditions make it work